Constructing a culturally empowering mathematics learning environment for EFL engineering students - Ward, Graeme Keith (Curtin University, 2010)
The emergence and evolution of constructivism since the early 1980’s has provided education and educational research with a new paradigm. The acceptance of this viewpoint has allowed educators greater scope as the criterion of epistemological and ontological truth / reality has been replaced by the more pragmatic approach of (practical) viability. This approach has, in turn, freed teachers to offer learning experiences which are useful and relate to previous experience and understanding of students rather than presenting rigorous and epistemologically correct information dissemination experiences.One area that has embraced constructivist principles in an effort to provide more relevant and cosmologically pertinent learning experiences has been the profession and learning of engineering.This thesis examines how engineering teachers can provide relevant learning experiences that recognize and connect with student past learning experiences and which meet the needs of modern learners, such as engineers, and in doing so develop these learners as problem solvers, communicators and team players who are aware of the wider implications and issues pertinent to the 21st century.In addition to looking at the problems faced and at how this researcher believes some of the issues can be resolved at the classroom and faculty level it also maps out the emergent transformative journey of this teacher-researcher that has emerged in the doing of this research, as I progress from what has been termed teacher mastery in the technical domain of human interest to what I perceive as the emancipatory.